Full body photobiomodulation therapy to induce faster muscle recovery in water polo athletes: Preliminary results - Zagatto, Alessandro M. [UNESP]; Dutra, Yago M. [UNESP]; Lira, Fabio Santos [UNESP]; Antunes, Barbara M. [UNESP]; Faustini, Julia B. [UNESP]; Malta, Elvis De S. [UNESP]; Lopes, Vithor H.F. [UNESP]; De Poli, Rodrigo A.B. [UNESP]; Brisola, Gabriel M.P. [UNESP]; Dos Santos, Giovanny V.; Rodrigues, Fabio M.; Ferraresi, Cleber (SAGE Publications, 2020)
Objective: To investigate the recovery of male water polo athletes applying full body photobiomodulation therapy (PBMT) regarding inflammation and muscle damage markers, testosterone and cortisol hormonal responses, heart rate variability (HRV), maximal voluntary contraction, and squat jump (SJ) after official water polo matches. Background: PBMT has been applied locally on specific muscle groups to induce faster recovery and improve the performance of athletes and nonathletes. However, many sports modalities require movement of the whole body, and a full body PBMT could be more adequate to irradiate large muscle areas homogeneously and faster. Methods: In a randomized, parallel, and double-blinded design, 13 athletes (whole team) aged 18 years attended the study and were allocated into two groups: PBMT (dose of 6.9 J/cm2, irradiance of 46.17 mW/cm2, 5 min irradiation) and placebo treatment. The study was conducted during the 2019 Brazilian under 20 water polo championship. All athletes were assessed by blood samples and neuromuscular evaluation. Immediately after each match, all athletes received PBMT (effective or placebo). Results: No significant interactions (raw values and percentage related to baseline) were observed for testosterone and cortisol, tumor necrosis factor-alpha, interleukin-6, creatine kinase concentration, maximal isometric voluntary contraction, SJ test, and HRV. Only an isolated interaction (decrease) was found for lactate dehydrogenase (LDH) response after the first match (p = 0.004, post-hoc p = 0.038). Conclusions: The parameters of the full body PBMT of this study did not induce faster recovery of inflammatory, muscle damage (excepting LDH), testosterone, cortisol, HRV, and neuromuscular responses during repeated days of water polo matches.
Keywords: Cortisol; Inflammation; Light-emitting diode; Low-level laser therapy; Testosterone